2022
DOI: 10.3389/fmolb.2022.822647
|View full text |Cite
|
Sign up to set email alerts
|

High-Coverage Serum Metabolomics Reveals Metabolic Pathway Dysregulation in Diabetic Retinopathy: A Propensity Score-Matched Study

Abstract: Background: Diabetic retinopathy (DR) is a major diabetes-related disease linked to metabolism. However, the cognition of metabolic pathway alterations in DR remains scarce. We aimed to corroborate alterations of metabolic pathways identified in prior studies and investigate novel metabolic dysregulations that may lead to new prevention and treatment strategies for DR.Methods: In this case-control study, we tested 613 serum metabolites in 69 pairs of type 2 diabetic patients (T2DM) with DR and propensity score… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In 2022, Guo et al. observed that compared with T2DM samples, the serum level of IAA in DR samples was significantly higher ( 34 ), which was consistent with our results of targeted and untargeted metabolomics. Through targeted metabolomics, we found that serum IAA levels in both NPDR and DR groups were significantly higher than those in T2DM group (AUC = 0.867, Figure 6B and AUC = 0.767, Figure 6C ), and our previous untargeted metabolomics studies also observed higher serum IAA level in DR group than T2DM group.…”
Section: Discussionsupporting
confidence: 89%
“…In 2022, Guo et al. observed that compared with T2DM samples, the serum level of IAA in DR samples was significantly higher ( 34 ), which was consistent with our results of targeted and untargeted metabolomics. Through targeted metabolomics, we found that serum IAA levels in both NPDR and DR groups were significantly higher than those in T2DM group (AUC = 0.867, Figure 6B and AUC = 0.767, Figure 6C ), and our previous untargeted metabolomics studies also observed higher serum IAA level in DR group than T2DM group.…”
Section: Discussionsupporting
confidence: 89%
“…According to the separate validation set, a panel of biomarkers consisting of phenylacetyl glutamine, nicotinuric acid, linoleic acid, and ornithine were developed to efficiently distinguish DR from T2DM. Recently, 613 serum metabolites (T2DM and DR), another similar case-control study conducted by Guo et al., were tested via UPLC-MS ( 87 ). They found a total of 89 featured metabolites by multiple statistical analyses, of which some new metabolic changes related to DR were identified, i.e., enhanced choline and indole derivatives, attenuated trehalose, etc.…”
Section: Metabolomics In Diabetic Retinopathymentioning
confidence: 99%
“…This multidimensional network biomarkers system may present the most effective means for identifying DR [61]. New DR-related metabolic changes, such as thiamine metabolic disorders, reduced trehalose, and increased choline and indole derivatives, were also revealed in another similar case-control study [62]. In order to gain further insights into the metabolic changes from T2DM to DR, Wang et al conducted comparative analyses of metabolic profiles across various stages, including NPDR and T2DM patients, PDR and T2DM patients, as well as DR and non-DR patients.…”
Section: Serum Metabolomicsmentioning
confidence: 80%